The Role of Tissue Macrophage-Mediated Inflammation on NAFLD Pathogenesis and Its Clinical Implications - Alisi, Anna; Carpino, Guido; Oliveira, Felipe L.; Panera, Nadia; Nobili, Valerio; Gaudio, Eugenio (Mediators of Inflammation, 2017)
The obese phenotype is characterized by a state of chronic low-grade systemic inflammation that contributes to the development of comorbidities, including nonalcoholic fatty liver disease (NAFLD). In fact, NAFLD is often associated with adipocyte enlargement and consequent macrophage recruitment and inflammation. Macrophage polarization is often associated with the proinflammatory state in adipose tissue. In particular, an increase of M1 macrophages number or of M1/M2 ratio triggers the production and secretion of various proinflammatory signals (i.e., adipocytokines). Next, these inflammatory factors may reach the liver leading to local M1/M2 macrophage polarization and consequent onset of the histological damage characteristic of NAFLD. Thus, the role of macrophage polarization and inflammatory signals appears to be central for pathogenesis and progression of NAFLD, even if the heterogeneity of macrophages and molecular mechanisms that govern their phenotype switch remain incompletely understood. In this review, we discuss the role of adipose and liver tissue macrophage-mediated inflammation in experimental and human NAFLD. This focus is relevant because it may help researchers that approach clinical and experimental studies on this disease advancing the knowledge of mechanisms that could be targeted in order to revert NAFLD-related fibrosis.